Effect of synthesis on the purity and particle size of ZrB2 powder - Gadakary S.; Davidson M.J.; Veerababu R.; Khanra A.K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present investigation, an attempt has been made to prepare ZrB2 powder by self-propagating high temperature synthesis (SHS) technique. The effect of synthesis on the purity and morphology of powder is investigated. A stoichiometric mixture of ZrO2, H3BO3 and Mg powder is synthesised in a resistance heating tubular furnace with continuous flow of high pure argon gas. The synthesis is also carried out with NaCl as a diluent. The MgO is leached out from the as-synthsised powder. Phase analysis of powder is performed by X-ray diffraction (XRD). Laser beam scattering technique is used to measure the particle size distribution. The morphology of powder is characterized by scanning and transmission electron microscopes. The XRD results show the presence of significant amount of unreacted ZrO2 phase in the product. The product is mixed with calculated amount of magnesium and boric acid and the mixture is synthesised further. There is a significant decrease of unreacted ZrO2 in the product after double synthesis. The SEM images show the presence of agglomeration of fine particles, whereas the TEM images show the decrease of particle size after double synthesis. To understand the synthesis process, the individual synthesis of ZrO2-Mg and H3BO3-Mg are also performed.